Ammonia Recovery from Industrial Wastewater by TransMembraneChemiSorption. Issue 8 (21st June 2013) - Ulbricht, Martin; Schneider, Jürgen; Stasiak, Maria; Sengupta, Amit; Wessling, Matthias
Abstract Membrane technology is a growing alternative for ammonia removal and recovery from wastewater compared to many other water treatment processes, such as strippers, scrubbers, and deaeration systems. Among the available alternatives, the TransMembraneChemiSorption (TMCS) has been gaining consideration, especially under certain operating conditions. TMCS using a membrane contactor is a unique separation process that is transitioning from research and pilot phases to field installations. This paper reviews the results of such an ammonia removal system using membrane contactors.